Econometric estimation of PCAIDS models - Germán Coloma (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2004)
This paper presents a version of the proportionally calibrated almost ideal demand system (PCAIDS) model, useful for merger simulations, which can be econometrically estimated using price data for two firms in a market. The model is then applied to a database of the Argentine gasoline market, and its results are compared to the ones obtained with other alternative specifications.
Keywords: C51; C33; L71; 330; PCAIDS; demand estimation; merger simulations; Argentine gasoline market